BENEISH M-SCORE MODEL UNTUK MENDETEKSI KECURANGAN KEUANGAN BUMN DI INDONESIA - Elsa Sari Yuliana; Yohanes Adi Nugroho; Murti Puspita Rukmi (Jurnal Inovasi Penelitian, 2021)
The development of the Beneish M-Score Model is carried out using data from public companies in the United States so that the calculated coefficients in the formula are not necessarily similar to the characteristics of public companies in Indonesia. even though this model has been widely used to see possible opportunities for companies in the Indonesian capital market. This causes the researcher to want to see whether the Beneish M-Score Model is accurate for use in the Indonesian capital market. The research objective is the accuracy of using the Beneish M-Score Model for public companies in the Indonesian capital market. And the research objective is to answer the two problem formulations. This form of research uses qualitative and quantitative methods. The type of data used is secondary data from the annual financial statements of public companies on the Indonesia Stock Exchange. Data collection techniques are carried out by documentation and literature study. Analysis technique with statistical approach